Epidemiology of Human Plague in the United States, 1900–2012 - Kugeler, Kiersten J.; Staples, J. Erin; Hinckley, Alison F.; Gage, Kenneth L.; Mead, Paul S. (Emerging infectious diseases, 2015)
We summarize the characteristics of 1,006 cases of human plague occurring in the United States over 113 years, beginning with the first documented case in 1900. Three distinct eras can be identified on the basis of the frequency, nature, and geographic distribution of cases. During 1900-1925, outbreaks were common but were restricted to populous port cities. During 1926-1964, the geographic range of disease expanded rapidly, while the total number of reported cases fell. During 1965-2012, sporadic cases occurred annually, primarily in the rural Southwest. Clinical and demographic features of human illness have shifted over time as the disease has moved from crowded cities to the rural West. These shifts reflect changes in the populations at risk, the advent of antibiotics, and improved detection of more clinically indistinct forms of infection. Overall, the emergence of human plague in the United States parallels observed patterns of introduction of exotic plants and animals.